Changes in paddy field management in Sindang Hamlet, Rancakalong Village, Sumedang District, West Java, Indonesia - RAHMI AULIA HIDAYAT; Ruhyat Partasasmita; JOHAN ISKANDAR; BUDI GUNAWAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hidayat R.A, Partasasmita R, Iskandar J, Gunawan B. 2020. Changes in paddy field management in Sindang Hamlet, Rancakalong Village, Sumedang District, West Java, Indonesia. Biodiversitas 21: 98-105. Farmers have traditional ecological knowledge related to the management of their fields, including knowledge of climate, soil types, soil fertility, various plants and animals, plant pests and irrigation. This knowledge is based on customs, beliefs and cosmos. Over time, government policies in agriculture such as the green revolution were implemented with the aim of increasing productivity of rice in wet-rice field farming. This initiated a change in the community's farming system from subsistence farming to commercial farming. Not to mention the existence of climate change that requires people to adapt. This change has an impact on ecological, economic and social aspects which are interesting to study. This study conducted in Sindang Hamlet, Rancakalong Village,  Sumedang District, West Java, which is known to have local rice cultivars and still practices rituals related to rice management. This study aims to analyze the changes in paddy management system in Sindang Hamlet due to green revolution and climate change, using qualitative data collection methods such as semi-structured interviews (deep interviews) with competent locals and participatory observations. Result of study showed that presently there are 3 groups of farmers in Sindang Hamlet, farmers who plant only local rice cultivars, farmers who plant only superior rice cultivars, and farmers who plant both local rice and superior rice cultivars in their land. Most farmers in Sindang Hamlet planted local rice but the diversity of local rice has decreased leaving only six cultivars, namely rayot, mesir, omas, torondol, mataram and randa kaya. There are still farmers in Sindang Hamlet who practice traditional farming, but many are starting to use modern tools and synthetic chemicals. The rice field management ritual called ngalaksa is still observed by the community, although there are some changes over time. The changes in rice field management have a negative impact on the local environment, economy and social aspects.